Projekt reformy finansów publicznych - zmiany organizacyjne - Woźniak, Barbara (The Draft Bill on Public Finance - Reform in Organizational Area Analysis, 2009)
The paper analyzes the draft of new bill on public finance - subsequent stage of public finances reform in Poland. The changes in the institutional arrangement and management of the sector are critically presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 371-378